2014
DOI: 10.1371/journal.pone.0103165
|View full text |Cite
|
Sign up to set email alerts
|

Parental Selection of Hybrid Breeding Based On Maternal and Paternal Inheritance of Traits in Rapeseed (Brassica napus L.)

Abstract: Parental selection is crucial for hybrid breeding, but the methods available for such a selection are not very effective. In this study, a 6×6 incomplete diallel cross was designed using 12 rapeseed germplasms, and a total of 36 hybrids together with their parental lines were planted in 4 environments. Four yield-related traits and seed oil content (OC) were evaluated. Genetic distance (GD) was estimated with 359 simple sequence repeats (SSRs) markers. Heterosis levels, general combining ability (GCA) and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…A positive correlation between TSW and SL was also observed with moderate coefficients in Li et al (2014) research. A negative correlation between TSW and SS were found by Xing et al (2014). The same correlation was also noticed in our research in 2014/15 growing season.…”
Section: Discussionsupporting
confidence: 90%
“…A positive correlation between TSW and SL was also observed with moderate coefficients in Li et al (2014) research. A negative correlation between TSW and SS were found by Xing et al (2014). The same correlation was also noticed in our research in 2014/15 growing season.…”
Section: Discussionsupporting
confidence: 90%
“…However, in the F 2 generation derived from reciprocal cross F 1 seeds, the difference in oil content disappeared. Also in the study by Xing et al (2014), the contribution of the maternal parent was slightly higher than that of the paternal parent with regard to the fat content. Other studies have indicated that embryo genetic effects, cytoplasmic effects and maternal effects as well as genotype×environment interaction effects (Wu et al 2006;Variath et al 2010) simultaneously controlled oil content in oilseed rape.…”
Section: Discussionmentioning
confidence: 64%
“…Maternal effects have been revealed for only the number seeds per pod. Xing et al (2014) showed that the number of seeds per pod is controlled by maternal Fig. 2 Distribution of DH lines from WC population characterised by yield and its components in the space of the two first canonical variates (V1 and V2).…”
Section: Discussionmentioning
confidence: 99%
“…Amiri-Oghan et al (2009) observed that this variable is controlled mainly by additive effects. However, according to Xing et al (2014), grain yield per plant is mainly controlled by the additive and epistatic effects. In this context, it can be inferred that the absence of heterosis is not decisive absence of dominance.…”
Section: Seed Yield Plant -1mentioning
confidence: 99%